2014
DOI: 10.1371/journal.pone.0087846
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Platform Metabolomic Analyses of Ergosterol-Induced Dynamic Changes in Nicotiana tabacum Cells

Abstract: Metabolomics is providing new dimensions into understanding the intracellular adaptive responses in plants to external stimuli. In this study, a multi-technology-metabolomic approach was used to investigate the effect of the fungal sterol, ergosterol, on the metabolome of cultured tobacco cells. Cell suspensions were treated with different concentrations (0–1000 nM) of ergosterol and incubated for different time periods (0–24 h). Intracellular metabolites were extracted with two methods: a selective dispersive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 124 publications
(174 reference statements)
1
53
0
Order By: Relevance
“…A similar study characterized the effect of ergosterol on N. tabacum c ells using non-targeted GC- and LC-MS (and other non-MS detection platforms), and found major metabolomic variation after 18 h of incubation with 300 nM ergosterol (Tugizimana et al, 2014). The major metabolic shifts occurred in secondary metabolites (terpenoids, coumarins, lignin precursors) and hormonal signaling molecules (jasmonate, salicylate-glucoside).…”
Section: Example Studies That Utilize Ms-metabolomics Workflows In Plmentioning
confidence: 97%
“…A similar study characterized the effect of ergosterol on N. tabacum c ells using non-targeted GC- and LC-MS (and other non-MS detection platforms), and found major metabolomic variation after 18 h of incubation with 300 nM ergosterol (Tugizimana et al, 2014). The major metabolic shifts occurred in secondary metabolites (terpenoids, coumarins, lignin precursors) and hormonal signaling molecules (jasmonate, salicylate-glucoside).…”
Section: Example Studies That Utilize Ms-metabolomics Workflows In Plmentioning
confidence: 97%
“…The DLLME procedure is based on the use of small volumes of an extraction and disperser solvent in aqueous samples. Only a single DLLME-GC×GC experiment has been reported: Tugizimana et al used DLLME-GC×GC-LR-ToF-MS for monitoring ergosterol-induced metabolite changes in Nicotiana tabacum cells [48]. Specifically, metabolic changes were correlated with modifications in defense-related metabolites.…”
Section: Dispersive Liquid-liquid Microextractionmentioning
confidence: 99%
“…There is limited evidence that secondary metabolites or small molecules from primary metabolism of microbes are also recognized. For ergosterol, a fungi-specific membrane sterol, it has been shown that nanomolar concentrations can elicit defense responses in tomato [22] and tobacco cells [23]. It is unclear whether fungal secondary metabolites also play a role as PAMPs and are recognized by cereal hosts.…”
Section: Secondary Metabolites and Pamp-triggered Immunitymentioning
confidence: 99%